Efektivitas Penggunaan Media Pembelajaran Al-Islam di SLBN 1 Yogyakarta - Habib Mustofa; Muhammad Excel Zarin Kalma; Nukhan Anwar; Akhmad Baharudin (Universitas Palan, 2024)
This research is based on researchers' searches on the effectiveness of Islamic learning media located in SLB N 1 Yogyakarta. Rooted in the problem, the researchers acquired some media that they felt were not optimal. Not a few media have been applied to teachers of Islam in order to encourage optimal student development. However, it is not easy for teachers to implement the media that has been designed as expected. Therefore, teachers are more dominant in applying learning media in a flexible way and adjusting each and every one of them. This research uses descriptive qualitative methods. The research methods used are observations, interviews, and documentation. The results of the research show that the Islamic learning media in SLB N 1 Yogyakarta has a positive impact on both students and teachers. Teachers and students have become more open and the Islamic learning system has become more structured with adequate media and learning methods. In addition, the system of admission of new students is implemented gradually to make it easier for students and teachers to carry out their studies. Each class listed also has its own grouping so that learning becomes more enjoyable and effective